Clinical outcomes of right ventricular outflow tract stenting compared to surgical shunting in late-presenting children - Prakoso, Radityo; Citra Dewi, Resi; Mendel, Brian; Atmadikoesoemah, Celly Anantaria; Purba, Salomo; Sakti, Damba Dwisepto Aulia; Iryuza, Nanda; Kurniawati, Yovi; Sukmawan, Renan (Frontiers in Cardiovascular Medicine, 2024)
Background: Right ventricular outflow tract (RVOT) stenting as an alternative palliation for patients with stenotic RVOTs is increasingly recognized. However, a notable gap remains in the literature regarding the efficacy and the comparative outcomes between RVOT stenting and the modified Blalock-Taussig shunt (mBTS) in children older than one year. Methods: We conducted a retrospective review of clinical data from patients aged one year to 18 years with stenotic RVOTs who underwent RVOT stenting or mBTS procedures at our institution between December 2019 and October 2022. We compared major adverse cardiovascular events (MACE) including re-hospitalization, re-intervention, and mortality, hospital and ICU length of stay, and discharge oxygen saturation between the groups. Results: We identified 58 patients (51.7% male) with a median age of 2.6 years (IQR: 2-8.1) and a median weight of 9.7 kg (IQR: 7.5-17.5). Among them, 18 (31%) patients received RVOT stenting, and 40 (68.9%) patients had mBTS. The median age for the RVOT stenting group was 92.5 months (IQR: 31.2- 152) compared to 26.5 months (IQR: 23.0-54.0) for the mBTS group (p=0.218). MACEs occurred in 4 (22.2%) patients with RVOT stents and 8 (20%) patients with mBTS (p=0.624). Patients with mBTS had a longer ICU stay (median 3.5 days, IQR, 2-5) compared to those with RVOT stents (median 2 days, IQR: 1-2) (p=0.295). Conversely, the hospital stay for patients with mBTS was shorter (median 10 days, IQR, 7.5-13.7) than for those with RVOT stents (median 11.5 days, IQR, 7-19) (p=0.045). The median discharge oxygen saturation was 87% (IQR: 83-88) in the mBTS group and 80% (IQR: 75-87) in the RVOT stenting group (p=0.212). Conclusions: RVOT stenting as palliation to stenotic RVOTs in children older than one year demonstrated outcomes comparable to mBTS in terms of MACE and achieving oxygen saturation targets.